2019
DOI: 10.1021/acs.chemrev.8b00520
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Landscape of Membrane-Permeabilizing Peptides

Abstract: Membrane permeabilizing peptides (MPPs) are as ubiquitous as the lipid bilayer membranes they act upon. Produced by all forms of life, most membrane permeabilizing peptides are used offensively or defensively against the membranes of other organisms. Just as nature has found many uses for them, translational scientists have worked for decades to design or optimize membrane permeabilizing peptides for applications in the laboratory and in the clinic ranging from antibacterial and antiviral therapy and prophylax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
183
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(214 citation statements)
references
References 533 publications
6
183
0
Order By: Relevance
“…Membrane permeabilization is the most common mechanism of antimicrobial peptide action. Researchers have proposed multiple models of peptides interacting with membranes . Based on our data, we have an interesting finding that zp3 seems to be more likely to attack the central region of the bacterial cell.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Membrane permeabilization is the most common mechanism of antimicrobial peptide action. Researchers have proposed multiple models of peptides interacting with membranes . Based on our data, we have an interesting finding that zp3 seems to be more likely to attack the central region of the bacterial cell.…”
Section: Resultsmentioning
confidence: 63%
“…Researchersh ave proposed multiple modelso fp eptides interacting with membranes. [36,42] Based on our data, we have an interesting finding that zp3 seemst ob em ore likely to attack the central region of the bacterial cell. In STEM images, we observed clear substance accumulation at the cell poles ( Figure 8A).…”
Section: Zp3 Showshigher Affinity For the Bacterial Cell Center And Lmentioning
confidence: 60%
“…A total of 3156 AMPs is listed in the APD, most of which were discovered in nature [13]. An analysis of 2700 of the 3156 AMPs in the APD showed that these peptides all have different structures and sequence motifs, and because they have a broad spectrum, they can kill a range of pathogens [42,43]. Interestingly, one-third of the AMPs are derived from frogs [44].…”
Section: Antimicrobial Peptide Databasementioning
confidence: 99%
“…Numerous approaches to peptide design have been introduced to make AMPs less toxic for humans while maintaining or improving their potency to eliminate bacteria [11,42], e.g., rational design [119,120], combinatorial peptide libraries [75,121], high-throughput screening [122,123], database-guided approaches [124,125], structure-function-guided design [86,126,127], and molecular dynamics simulations [44]. Three major methods to improve AMP function have been described: (i) High-throughput screening can be used to identify potential AMPs [128][129][130].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…4A), and putatively modulate their permeability (42) in what is known as carpet model (61). The mechanism by which such an interaction could cause a transient permeabilization is still a matter of debate, although the asymmetric distribution on the membrane bilayer has been pointed out as plausible reason (62). Further experimental work with the identified proteins could shed light on the potential transport mechanism.…”
Section: Metabolite Transportmentioning
confidence: 99%